Delineation of competence between public authorities in the field of legal regulation of institutions of municipal democracy - Svetlana V. Narutto (Правоприменение)
The subject of the article is the issues determining the level of legal regulation of instruments of direct municipal democracy.The purpose of the article is to analyze the judicial practice, especially of the Constitutional Court of the Russian Federation, related to the problems of differentiation of normative competence in the field of municipal democracy between the Federal, regional and municipal levels of government.The methodology of the study includes systematic approach, formal logical method, interpretation of judicial decisions of Russian Constitutional Court. The issues of determining the level of legal regulation of instruments of direct municipal democracy – elections, referendum, recall of an elected person, voting on changes in the boundaries of the municipality and the transformation of the municipality – are analyzed through the prism of judicial practice.The main results and scope of their application. The Constitutional Court of the Russian Federation has developed many common positions that can be applied in determining the parameters of rule-making on issues of direct democracy. The Constitutional Court of the Russian Federation confirms the broad competence of the constituent entities of the Russian Federation in the regulation of municipal elections. However, the expansion of the normative competence of the constituent entities of the Federation does not always lead to the democratization of the subject of municipal regulation. The federal and regional public authorities must take into account the interests of municipalities in carrying out the legal regulation of a constituent entities’ matter, and leave them the possibility of legal regulation, including the implementation of direct democracy at the local level. The territorial foundations of local self-government, formation of municipal entities, on the one hand, and the administrative-territorial division of constituent entities of the Russian Federation on the other, have independent significance, its own legal content and belong to different spheres: the first belongs to joint conducting by Russia and its constituent entities, the second belongs to the exclusive jurisdiction of the constituent entities of the Russian Federation.Conclusions. The conclusions formulated by the Constitutional Court of the Russian Federation in relation to the distribution of legal regulation between the levels of power, the definition of the parameters of municipal rule-making on issues of direct democracy are summarized and commented.